Effectiveness and operability of different screening methods for diabetes in community populations: a comparative analysis - Yan-yun LI; Si-yuan WANG; Qin-ping YANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo evaluate the efficiency and practical significance of different diabetes screening methods in community population and to provide evidences for the establishment of community diabetes screening process. MethodsUsing multistage cluster random sampling, we recruited 23 940 permanent residents aged ≥ 35 years and without acute or serious chronic diseases/type I diabetes in urban communities and rural villages of 7 districts of Shanghai for a questionnaire survey, physical examination and blood glucose measurement during October - December, 2017. The effectiveness and operability of an early-detecting process, risk score assessment and fast plasma glucose (FPG) screening for type 2 diabetes (T2DM) were evaluated by comparing the three methods' sensitivity, specificity, Youden index , area under the receiver operating characteristic curve (AUROC), the proportion of abnormal FPG and oral glucose tolerance test (OGTT). ResultsOf the 17 981 previously undiagnosed diabetics identified among the residents and included in the analysis, 4 129 prediabetics and 2 213 diabetes were detected, with the prevalence rates of 22.96% and 12.31%, respectively. For the three methods (early-detecting process vs. risk score assessment vs. FPG screening) in detections of diabetes/prediabetic in previously undiagnosed diabetic population, the sensitivities (%) were 87.3/61.0 vs. 96.7/93.3 vs. 82.5/47.8; the specificities (%) were 60.2/58.9 vs. 15.2/15.8 vs. 87.5/86.0; the Youden indexes were 0.479/0.199 vs. 0.119/0.091 vs. 0.700/0.338, and the values of AUROC were 0.858/0.620 vs. 0.680/0.602 vs. 0.922/0.708; also for the three methods, the proportions (%) of the examinees requiring FPG/2-hour plasma glucose detection of OGTT were 45.7/42.6 vs. 86.3/86.3 vs. 100/21.1, respectively. ConclusionIn diabetes screening among community residents, early-detecting process could achieve a higher detection rate of abnormal glucose metabolism with a minimum number of venous blood glucose detection and simplified on-site implementation procedures and the process could be adopted effectively in large-scale prediabetics and diabetes screening in community populations.